Unveiling the functional diversity of ionotropic glutamate receptors in the Pacific oyster (Crassostrea gigas) by systematic studies - Zhang, Xueshu; Zhang, Linfang; Si, Yiran; Wen, Xue; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2023)
Ionotropic glutamate receptors (iGluRs), pivotal in mediating excitatory neurosignals within the central nervous system, are instrumental in environmental stress responses. In this investigation, 12 iGluRs identified in the Pacific oyster are herein designated as CgiGluRs, and further categorized into three distinct subfamilies based on their transmembrane domains. Cross-species evolutionary analysis unveiled a high degree of conservation in the sequence and structural attributes of these CgiGluRs. These receptors are ubiquitously distributed across various tissues, with pronounced expression in the oyster’s mantle, labial palps, and gills, underlining their integral role in the oyster’s environmental sensing mechanisms. Post the D-shaped larval stage, a marked upward trend in CgiGluRs expression was observed, denoting their critical involvement in oyster development beyond this phase. Exposure to five metals—cadmium (Cd), copper (Cu), zinc (Zn), mercury (Hg), and lead (Pb)—elicited a significant upregulation of CgGRIA4 expression, indicating a robust response to metal stress. A KEGG enrichment analysis on 142 genes, exhibiting parallel expression trends with CgGRIA4 under metal stress, suggests that CgGRIA4 could augment excitatory signal transmission by activating glutamatergic and dopaminergic synapses, thereby contributing to the metal stress response in the oyster. This inquiry not only bolsters our comprehension of the iGluRs gene family in metal stress response but also paves the way for future exploration of its cardinal role in cellular signaling and environmental adaptability.